Bank lending behaviour and macroeconomic factors: A study from strategic interaction perspective. Issue 11 (November 2022) - Le, Huong Nguyen Quynh; Nguyen, Thai Vu Hong; Schinckus, Christophe
Abstract: This study investigates the moderating role of strategic interaction on the relationship between bank lending and macroeconomic factors, using panel data on Vietnamese commercial banks over 2008–2018. We find that the effect of macroeconomic and monetary policy shocks on bank lending behaviour is less pronounced when banks engage in a less competitively aggressive environment. The study contributes to the literature of bank lending by incorporating macroeconomic environment and micro (strategic interaction)-level to analyze the lending behaviour of an individual bank. Since the analysis of macroeconomic factors alone is insufficient to explain the aggregate relationships in the model of banking, understanding the nature of strategic interaction is essential to predetermine how bank lending behaviour relates to the transmission mechanism of monetary policy. Highlights: The effects of the interaction of macroeconomic factors (specialized in GDP growth and policy interest rate) with the strategic interaction on bank lending behaviour are examined. Banks competing in strategic substitutes will restrict lending activities in periods of economic expansion. The impact of monetary policy shocks on bank lending behaviour is less pronounced under a less competitively aggressive environment. Abstract : Strategic interaction; Bank lending; Vietnamese banks; Monetary policy.